Extension and adaptation of the Flor da Rosa Monastery into a pousada, Crato (1990–1995/2007–2009) - Sequeira, M. (Flashback: Carrilho da Graça, 2022)
In 1990, the ENATUR national tourism company commissioned Carrilho da Graça for the extension and adaptation of the Flor da Rosa Monastery, which was to serve a new function as a pousada (inn). Carrilho da Graça aimed to consolidate the church and cloister, to discreetly restore the rest of the monastery, where some new facilities would be installed, and mainly to add a new building with 13 rooms to the north. The new building responded almost entirely to ENATUR’S brief, freeing the original monastery building from a series of heavy interventions and maintaining public access to almost all its areas. It is now widely agreed that this operation was one of the most paradigmatic built-heritage interventions of the end of the last century in Portugal, in which a model was created based on the formal, constructive and material independence of the new intervention.